Sebelum Islam:Evolusi Sosial dan Budaya Arab dibawah Pengaruh Romawi dan Persia - Mudin, Imam; Zuhriyah, Siti; Maesaroh, Maesaroh; Haetami, Muhamad; Kurniawan, Kurniawan (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This research examines the social and cultural evolution of pre-Islamic Arab society through an in-depth analysis of the influence of the Roman and Persian Empires. The main focus of this research is to explore the structural changes that occurred in Arab society before the emergence of Islam, by considering the complex dynamics of interethnic interactions, trade systems, and cultural practices. This research uses an interdisciplinary approach that combines the perspectives of archaeology, historical anthropology, and geopolitical studies to reveal complex mechanisms of social change. The research results show that pre-Islamic Arab society had a very dynamic and adaptive social structure. The initially rigid tribal system experienced significant changes due to interactions with large empires, economic exchange, and the process of cultural acculturation. This study confirms that the pre-Islamic period was not just a transitional period, but was an important phase in the formation of the social and cultural identity of Arab society. The findings of this research provide a significant contribution to understanding the complexity of the history of the Arab region, as well as dismantling conventional narratives that tend to simplify the social dynamics of that period.